Entrepreneurial Mindset for Sustainable Economic Growth: Gen Z Jabodetabek Case - Tan, Pauline H. Pattyranie; Wilson, Nicholas; Novembri, Christian S. R. (Indonesian Journal of Sustainability Accounting and Management, 2025)
Entrepreneurship education is increasingly associated with inclusive and sustainable economic growth, especially if it is easily accessible, value-based, and tailored to Generation Z’s learning preferences. Access to entrepreneurship education is considered essential in shaping an entrepreneurial mindset for innovation and sustainable economic development. This study aims to analyze the effect of Entrepreneurship Education on Self-Efficacy, the effect of Entrepreneurship Education on Entrepreneurial Attitudes, the effect of Self-Efficacy on entrepreneurial attitudes, the effect of Entrepreneurial attitudes on Entrepreneurial Mindset, the effect of Entrepreneurship Education on Entrepreneurial Mindset, and the effect of Self-Efficacy on Entrepreneurial Mindset of Gen Z. The novelty of this research is the integrative approach between theory and practice for Gen Z in Indonesia, by combining classical theories such as the Theory of Planned Behavior (TPB) with contemporary realities, especially entrepreneurial education and self-efficacy that are tailored to the values and learning preferences of Generation Z. For practical contribution, this research provide a basis for developing an entrepreneurship curriculum based on a mindset. The quantitative analysis was conducted on 160 respondents from Generation Z who have studied Entrepreneurship, as well as those who intend to and have acted as entrepreneurs, both in family businesses and non-family businesses. The findings of this study are that Entrepreneurship Education has a positive effect on Self-Efficacy, as accepted. Entrepreneurship Education has a positive effect on Entrepreneurial Attitudes, as accepted. Self-efficacy has a positive effect on Entrepreneurial Attitudes, rejected. Entrepreneurial Attitude has a positive effect on Entrepreneurial Mindset, as accepted. Entrepreneurship Education has a positive effect on Entrepreneurial Mindset, as accepted. Self-efficacy has a positive effect on Entrepreneurial Mindset, as rejected.